Mula sa mga pakpak ng entablado : poetika ng dulaang kababaihan - Barrios, Joi. 4 0 16; 5 (Diliman, Quezon City : University of the Philippines Press, 2006)
Study of women's stage play writers including their writings and history of women's drama.
Includes bibliographical references (p. 299-310).
In Tagalog.
Keywords: 2 -- 0; 6; History and criticism.;Women authors. -- Tagalog drama;Tagalog drama;Women in literature.;Verse drama, Filipino.;Philippine drama; 20; 2